Taxonomic review and delimitation of species boundaries of Leucopholis Dejean (Coleoptera Scarabaeidae: Melolonthinae: Leucopholini) associated with Areca catechu L. (Areca Nut) in South India - Prakash, Kunthanahalli V.; Yeshwanth, Hesaraghatta M.; Lakshminarayanan, Shayamal; Cabusas, John Vincent B.; Calcetas, Orlando A. (2024)
The white grubs of the genus Leucopholis Dejean are the most devastating insect pests of areca nut and coconut palms in south India. To date, three species, L. lepidophora Blanchard, 1851, L. coneophora Burmeister, 1855, and Leucopholis burmeisteri Brenske, 1894 have been reported from Karnataka. Leucopholis lepidophora is distinct from the two species based on their genitalia male and molecular markers. An average of 3.43–15.4% genetic distances were observed among L. coneophora and L. burmeisteri species based on the mitochondrial COI gene DNA barcode region. These results imply that they belong to distinct species. A key to the species of Leucopholis in south India is also provided.
Keywords: Insect pests